Study on the Prognostic Factors Related to Endovascular Treatment of Acute Basilar Artery Occlusion Within 24 Hours of Onset - Changchun Jiang; Yu Fan; Yuechun Li; Wei Ma (Journal of Investigative Surgery, 2025)
Background To evaluate the prognostic effect of endovascular treatment (EVT) in patients with acute base artery occlusion (ABAO) within 24 h of onset, and analyze the factors related to prognosis.Methods A retrospective analysis was conducted on all ABAO patients who received EVT within 24 h of onset in the neurology department of Baotou Central Hospital in Inner Mongolia from May 2016 to October 2022. Good prognosis was defined as a Modified Rankin Scale (mRS) score of 0–3 and poor prognosis mRS score of 4–6 at 90 day follow-up, and factors related to prognosis were analyzed.Results Among the 77 patients included in the analysis, 68 patients (88.3%) achieved recanalization (modified thrombolysis in cerebral infarction, mTICI 2b/3 grade). Thirty eight patients (49.4%) achieved an overall good prognosis. In univariate analysis, age, baseline Glasgow Coma Scale (GCS), baseline National Institutes of Health Stroke Scale (NIHSS), posterior circulation Acute Stroke Prognostic Early CT score (pc ASPECTS), preoperative intravenous thrombolysis, and mTICI2b-3 were factors affecting good prognosis. Multivariate analysis showed that shorter onset to puncture time (OR 0.069; 95% CI, 0.009–0.519; p = 0.009), lower NIHSS (OR 1.179; 95% CI, 1.019–1.364; p = 0.027), and higher pc ASPECTS (OR 0.489, 95% CI, 0.250–0.959, p = 0.037) were factors influencing good prognosis in this study.Conclusions In summary, endovascular treatment for patients with acute basilar artery occlusion is safe and effective, but EVT may achieve better prognosis within 6 h of onset. The shorter time from onset to puncture at admission, lower baseline NIHSS score, and higher baseline pc-ASPECTS are factors affecting the good prognosis of patients at 90 days.